2017
DOI: 10.15760/trec.166
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Evaluation of Transportation Structures with iPod-Based Data Acquisition

Abstract: This grant supported coursework and laboratory development and expanded research capacity, promoting (a) innovative learning activities that expose students to cutting-edge methods of bridge structural health and behavior monitoring and (b) research by our growing group of graduate students using developing technologies (specifically, shake tables and iPods with on-board accelerometers). As transportation infrastructure reaches and exceeds its design life, engineering efforts are turning to evaluation, rehabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Response measurement was conducted using iPods, based on the positive results of previous NITC-funded education research. iPods had proven to be sufficiently accurate for classroom and lab use, and appeared to have sufficient accuracy and precision to function as well in field tests (Riley, 2017). Others have found similar results (see studies by Shrestha et al; and Morgenthal, Hopfner, and Feng).…”
Section: Ipod-based Systemmentioning
confidence: 74%
See 1 more Smart Citation
“…Response measurement was conducted using iPods, based on the positive results of previous NITC-funded education research. iPods had proven to be sufficiently accurate for classroom and lab use, and appeared to have sufficient accuracy and precision to function as well in field tests (Riley, 2017). Others have found similar results (see studies by Shrestha et al; and Morgenthal, Hopfner, and Feng).…”
Section: Ipod-based Systemmentioning
confidence: 74%
“…Results from previous research demonstrated the accuracy of iPod accelerometers as well as the limits of their precision (Riley, 2017). Additional work by graduate student, Samuel Lozano, to measure iPod accelerometer precision and compare it to a reference accelerometer and vision sensing measurements is included in the unpublished draft paper in Appendix A-1.…”
Section: Evaluation Of Ipod Accelerometersmentioning
confidence: 99%
“…Others have used mobile devices to teach principles of structural damage detection [5] and have identified mobile devices as a potential means to crowdsource structural response data for to support learning activities as well as infrastructure management [6]. Some researchers are finding that mobile devices may serve as effective data collection tools in the field [6,7,8]. With respect to teaching experimental modal analysis to undergraduates, Peter Avitabile [9] described the value of color and multimedia but did not address laboratory or field experimentation.…”
Section: Introductionmentioning
confidence: 99%